The formation of national identity in process of aesthetic education of youth - Safina, Gulnara Ildarovna; Pushkar, Taisiya Olegovna; Yao, Lubov Markelovna; Emanova, Juliana Gennadievna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The paper discusses the issues of national identity, and patriotism formation by means of national art and folk culture, which are able to arouse love for the family, their home, their national and territorial community. To study the process of formation of national identity, a constructionist approach was taken, within which a constructed phenomenon was considered. The identity system of modern youth was studied by compiling a test by T. Kuhn and T. MacPartland "Who Am I?" The test was offered to students of Kazan National Research University (1997; 2012), and students of Kazan Federal University (2019). A tendency to increase the proportion of students who determined their national identity (Tatar man / Tatar woman, Russian man / Russian woman) was identified. The paper reveals specific examples of the methods of forming a national identity in the process of aesthetic education: the revival of folk art, since it is inextricably linked with national and religious traditions; familiarization with the arts and crafts, reflecting the distinctive features of each nation. All the peoples of the Middle Volga live in Tatarstan: except for Tatars and Russians, the Chuvash, Mari, Mordovians, Ukrainians, Belarusians live in the republic. All nationalities of the republic have formed their institutional formations, or cultural-national communities, spend their holidays, which go beyond the framework of the republican and become all-Russian and international.